The Value of the Middle Meningeal Artery in Cerebrovascular Bypass Surgery: An Anatomic Feasibility Study. Issue 1 (22nd July 2018) - Niknejad, Hamid Reza; van der Zwan, Albert; Heye, Sam; Van Calenbergh, Frank; Van Loon, Johannes
Abstract: BACKGROUND: Over the past decade, there has been a revival and a renewed interest for cerebrovascular bypass procedures. The superficial temporal artery (STA) has its value as a reliable donor vessel; however, a possible role for the middle meningeal artery (MMA) as a donor artery is still unclear. OBJECTIVE: To assess the feasibility of using the MMA as a donor vessel in cerebrovascular surgery. METHODS: We performed cadaveric dissections on 12 fresh specimens (23 sides) after bilateral silicone injection into the internal and external carotid arteries. We compared the size, diameter, and possibility to perform a bypass to the middle cerebral artery for both the MMA and the STA. Measurements were done using an electrical caliper. Additional measurements of the MMA and STA were performed on 20 random angiograms. RESULTS: There was no statistically significant difference in diameter of the MMA at its ostium being 2.4 mm, compared to 2.7 mm for the STA ostium ( t -test; P = .21). The MMA could be mobilized over 4.1 cm, whereas the STA over 8.3 cm. Finally, the mean diameter of the donor vessel at the site of the anastomosis was 1.6 mm versus 1.9 mm for MMA and STA, respectively ( P = .0026). We were able to perform an MMA and middle cerebral artery anastomosis on 17 sides. CONCLUSION: These results suggest that the MMA is a potentially valuable donor vessel to be used in selected cases. The availability of a suitable MMA branch should be assessed preoperatively on the angiogram.